Persistence of SARS-CoV-2 N-antibody response in healthcare workers, London, UK - Shrotri, M; Harris, RJ; Rodger, A; Planche, T; Sanderson, F; Mahungu, T; McGregor, A; Heath, PT; Brown, CS; Dunning, WJ; Hopkins, S; Ladhani, S; et al. (Centers for Disease Control and Prevention, 2021)
Prospective serosurveillance of severe acute respiratory syndrome coronavirus 2 in 1,069 healthcare workers in London, UK, demonstrated that nucleocapsid antibody titers were stable and sustained for <12 weeks in 312 seropositive participants. This finding was consistent across demographic and clinical variables and contrasts with reports of short-term antibody waning.